Evaluation of water-user performance in smallholder irrigation schemes in KwaZulu-Natal Province, South Africa: A stochastic meta-frontier analysis - Phali, Lerato; Mudhara, Maxwell; Ferrer, Stuart; Makombe, Godswill (Frontiers in Sustainable Food Systems, 2022)
Smallholder Irrigation Schemes (SIS) are pivotal in sustaining livelihoods and creating employment in rural communities of South Africa. However, despite the revitalization and rehabilitation of SIS by the government, the performance of farmers is still below par. This study evaluates the performance of water-users across four SIS in KwaZulu-Natal Province (KZN). Technical Efficiency was used as a proxy for performance and the Stochastic Meta-Frontier Analysis method was employed to measure the overall efficiency across 306 households. The efficiency model results showed that governance index, psychological capital, land tenure security, credit access and gender affect water-users' technical efficiency. The study concludes that interventions should be geared toward strengthening institutions and the empowerment of farmers through relevant training and access to credit. Furthermore, adequacy of water and its availability in the schemes should be improved to ensure profitability and productivity of water.